1999
DOI: 10.1111/j.1600-065x.1999.tb01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative organization and function of the major histocompatibility complex of domesticated cattle

Abstract: This review focuses on recent advances in research on the bovine major histocompatibility complex (BoLA), with specific reference to the genetic organization, polymorphism and function of the class II genes. The BoLA region is unlike the MHC of humans and mice in that a large inversion has moved several class II genes, including the TAP/LMP cluster, close to the centromere of bovine chromosome 23. Therefore, close linkage of MHC genes and other genes associated with the MHC in humans and mice does not appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 77 publications
(44 reference statements)
3
83
0
1
Order By: Relevance
“…Examples of rearrangements documented in the few species that have been studied include inverted translocation involving part of the class II region together with a large piece of the chromosome in cattle (reviewed in Ref. 55), apparent removal of the class III region from the Mhc of the rabbit (56), translocation of two class I loci to the class II region in the mouse (reviewed in Ref. 1), and the contraction of much of the Mhc region to a segment of Ͻ100 kb and a pericentric duplication of the Mhc in the domestic fowl (11).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of rearrangements documented in the few species that have been studied include inverted translocation involving part of the class II region together with a large piece of the chromosome in cattle (reviewed in Ref. 55), apparent removal of the class III region from the Mhc of the rabbit (56), translocation of two class I loci to the class II region in the mouse (reviewed in Ref. 1), and the contraction of much of the Mhc region to a segment of Ͻ100 kb and a pericentric duplication of the Mhc in the domestic fowl (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between immune response and these ovine MHC-DR molecules remains unknown. In BLV infection, several previous studies (23,26,48) revealed the presence of the amino acids Glu-Arg (ER) at positions 70-71 of the bovine leukocyte antigen (BoLA)-DRβ chain associated with resistance to PL in cattle (48). Furthermore, it appeared that BoLA-DRB3 alleles encoding Glu, Arg and Val at positions 74, 77 and 78 of the BoLA-DRβ chain might be related to resistance to tumor development (1).…”
mentioning
confidence: 99%
“…Although the role played by the BLV Tax is unknown, it has, nevertheless, been shown to enhance nuclear protooncogene such as c-fos [19]. Both genetic and immunological factors contribute to susceptibility to BLV-induced disease progressions [3,26]. In genetic analysis of BLV-infection, previous studies revealed the polymorphism in bovine leukocyte antigen (BoLA)-DRβ chain associated with resistance to expansion of BLV [27] and PL [28].…”
mentioning
confidence: 99%